Optimizing a microwave gas ion source for continuous-flow accelerator mass spectrometry - von Reden, K. F.; Roberts, M. L.; Burton, J. R.; é, S. R. (Review of Scientific Instruments, 2012)
A 2.45 GHz microwave ion source coupled with a magnesium charge exchange canal (C × C) has been successfully adapted to a large acceptance radiocarbon accelerator mass spectrometry system at the National Ocean Sciences Accelerator Mass Spectrometry (AMS) Facility, Woods Hole Oceanographic Institution. CO2 samples from various preparation sources are injected into the source through a glass capillary at 370 μl/min. Routine system parameters are about 120–140 μA of negative 12C current after the C × C, leading to about 400 14C counts per second for a modern sample and implying a system efficiency of 0.2%. While these parameters already allow us to perform high-quality AMS analyses on large samples, we are working on ways to improve the output of the ion source regarding emittance and efficiency. Modeling calculations suggest modifications in the extraction triode geometry, shape, and size of the plasma chamber could improve emittance and, hence, ion transport efficiency. Results of experimental tests of these modifications are presented.